How do you simplify 2x(x^2-3)?

2 Answers
Apr 17, 2017

See the entire solution process below:

Explanation:

To simplify this expression multiply each term within the parenthesis by the term outside the parenthesis:

color(red)(2x)(x^2 - 3) = (color(red)(2x) xx x^2) - (color(red)(2x) xx 3) = 2x^3 - 6x

Apr 17, 2017

2x^3-6x

Explanation:

Apply the distributive property

color(red)(2x)(x^2-3)=color(red)(2x)(x^2)-color(red)(2x)(3)

color(red)(2x) is the same as color(red)(2x^1)

So color(red)(2x)(x^2)-color(red)(2x)(3)=color(red)(2x^color(green)1)(x^2)-color(red)(2x)(3)

To multiply color(red)(2x^color(green)1) and x^2 add the exponents of the x terms, so,

color(red)(2x^color(green)1)(x^2)=2x^(color(green)1+2)=2x^3

color(red)(2x^color(green)1)(x^2)-color(red)(2x)(3)=2x^3-6x

This is your final answer (it cannot be simplified furthermore)